Avaliação do efeito do resveratrol sobre os tecidos periodontais de ratos com obesidade induzida pelo glutamato monossódico e submetidos à periodontite experimental - Pasqualotto, Lais Fernanda (2019)
Several scientific studies have suggested that obesity contributes effectively to the severity of periodontal disease. On the other hand, resveratrol, a polyphenol well known for its health benefits, can prevent obesity and interfere positively with osteoblastogenesis and promote immunomodulatory effects on host response in the presence of periodontal disease. Thus, the objective of this study was to evaluate the appearance of periodontal tissues under the effects of administration of resveratrol by means of morphological and radiographic analyzes in rats with obesity and experimentally induced periodontitis. 48 rats were used. During the first five days of life, half of the animals received injections of monosodium glutamate at 4 g / kg body weight, forming the Obesity group, the other half of the animals received 0.9% saline injections at 1.25 g / kg, during the same period forming the Control group. At 21 days of age weaning was performed. At 75 days of age, half of the animals in each group (n = 12) were submitted to induction of experimental periodontitis, forming the ligation groups. After this procedure, 8 groups (n = 6) were generated: 1) Control Group (CON), 2) Obesity Group (OBS), 3) Resveratrol Group (RSV), 4) Ligature-Obesity Group (LIG-OBS), 6) Ligation-Resveratrol Group (LIG-RSV), 7) Obesity-Resveratrol Group (OBS-RSV), 8) Ligature-Obesity-Resveratrol Group. The animals belonging to the Resveratrol groups received a dose of 10 mg / kg body weight of the polyphenol orally for 4 weeks starting at 78 days of age. After the 105 days of the experimental period, obesity was evaluated and euthanasia was performed, where blood was collected and triglyceride and total cholesterol concentrations were determined. Hemimandibula were also collected for histological and radiographic analysis, gingival tissue samples for immunological analysis and histological analysis of the abdominal aorta artery, in order to evaluate the effects induced by obesity and resveratrol. Obesity was confirmed by the Lee index and by the retroperitoneal and perigonadal fats (p <0.05). In the analysis of bone tissue, a more pronounced alveolar bone loss was observed in the LIG group, with a decrease in bone loss in the LIGRSV and LIGOBS groups. In the gingival tissue, all animals that underwent experimental periodontitis presented a statistically significant difference when compared to the animals that did not receive the ligature. Obese animals also had higher levels of triglycerides and cholesterol than the other animals, and those who received the diet with resveratrol had a reduction in these patterns. In the morphometric analysis of the abdominal aorta, the thickness of the arteries was statistically different in all groups, and the LIGOBS group had the greatest thickness (p <0.05), however, with respect to the artery area, the CON group presented the largest area and the LIG and LIGOBS groups the smallest area. Thus, it is possible to suggest that the obesity model and resveratrol, act with protective effect of alveolar bone loss induced by ligature. Also, it can be observed that the association between obesity and periodontitis may contribute to an increase in abdominal aortic thickness.